The neoliberal rationality in producing discourses on financial education in didactic collections of the New High School - Silva, Francisco Vieira da; Costa, Wyllamy Samuel da (Revista Hipótese, 2023)
The article analyzes how neoliberal rationality marges on constructing discourses about financial education in didactic collections of the New High School. Thus, it takes as a theoretical contribution the investigations of Foucault (2008; 2010), Dardot and Laval (2016), and Saraiva (2017), among other authors. As for the methodology, this is a descriptive-interpretative study of a qualitative approach. The corpus comprises statements extracted from two Applied Human and Social Sciences textbooks in dialogue with Mathematics and its Technologies, approved by the National Plan of Books and Teaching Materials (PNLD), 2021 edition. The analyses allow us to see that the discourses on financial education are anchored in an ideal personal and family income model, amenable to planning, saving, and investment, which do not dialogue with the objective conditions of Brazilian students and their families to silence the existing social inequalities.
Keywords: Discourse; Neoliberal rationality; Financial education; New High School